PENGEMBANGAN SISTEM INFORMASI PENANGANAN PENDERITA GANGGUAN JIWA DENGAN PENDEKATAN ENTEPRISE SYSTEMS - Cokorda Pramartha; I Made Widhi Wirawan (SINTECH (Science and Information Technology) Journal, 2022)
The health information system is a digital system that is quite complex so that in the development and evaluation stages, it is necessary to consider cultural, political, social and organizational structure factors. In Bali, the number of people with mental disorders is considered high and the need for treatment is in a fairly long time, that is the reason a management information system is needed to organize data and information about the patients. This study aims to develop a centralized management information system that can be utilised specifically for health workers to manage information regarding people with mental disorders. The development of the management information system in this study involves doctors, volunteers, and admin or organizational staff in every critical process. The prototyping method was chosen as a system development method because it considered more adaptive in capturing the needs of prospective system users.  At the evaluation stage, functional evaluation through the Black-box method was used to test the functional capabilities of the system. In addition, Technology Acceptance Model (TAM) and Task Load Index (TLX) were used to evaluate the non-functionality of the system where all users agree that the developed management information system is useful, easy to use, and requires a small cognitive workload.